TRAINING YOUNG RESEARCHERS AT THE POSTGRADUATE LEVEL: IN SEARCH OF A GOAL - Natalia G. Popova; Ekaterina V. Biricheva (Высшее образование в России)
Abstract. In this paper, we attempt to find a common ground for the practical realization of new postgraduate training standards in Russia that are aimed at increasing the quality of Russian postgraduate education. Serious concerns have been recently expressed regarding the inconsistencies in the introduced standards and the need to substantially revise existing normative documents that regulate the postgraduate study system. However, although these thorny institutional issues are of great importance, academic supervisors and PhD programme teachers need to realize postgraduate syllabi in the here and now. Therefore, in order for the postgraduate study system to meet all the modern requirements, an adequate pedagogical model and reliable reference points should be determined. A social and philosophical analysis was carried out to examine the modern reality of young researchers and to outline a framework for the modernization of the existing postgraduate study system. The results of a survey conducted across the Institutes of the Ural Branch of the Russian Academy of Sciences to examine the perceptions of PhD students regarding the new programmes are presented and discussed. It is concluded that a sufficient level of academic awareness as a “researcher” and “teacherBresearcher” developed in postgraduate students may become an integrated pedagogical goal at this educational stage. The paper may be of interest to a wide readership of sociologists of science, PhD programme teachers, as well as to researchers concerned with contemporary issues faced by the Russian educational system and Russian science.